The Influence of Headmaster Leadership Style on Teacher Performance - Sukmawati, Sukmawati; Jamaluddin, Jamaluddin; Niswaty, Risma; Asmanurhidayani, Asmanurhidayani (Universitas Negeri Makassar, 2018)
The headmaster as a leader in a school has a very important role. This study aims to determine the effect of the headmaster leadership style on teacher performance at State Vocational School 1 Gowa. This research is quantitative research. Respondents were all teachers of State Vocational School 1 Gowa. Data collection techniques used through observation, questionnaires (questionnaires), interviews and documentation. Data obtained from the results of the study were processed using data analysis techniques consisting of descriptive analysis techniques and inferential statistical analysis. The results showed that the influence of the leadership style of the principal of the State Vocational School 1 Gowa Â was in a very good category with a percentage rate of 84.03 percent, and for the teacher performance of the State Vocational School 1 Gowa included in the very good category with a percentage rate of 84.49 percent. This can be proven by the results of the moment product correlation analysis of 0.280, which means the level of relations in the low category. It can be concluded that there is a Positive and Significant Influence of the influence of headmaster leadership style on the performance of teachers at State Vocational School 1 Gowa, seen from several indicators of leadership variables, namely directing style coaching style, and supporting style. Teacher performance variables, namely as learning designers, as instructors of learning, as managers of learning, as counselors, as evaluators, and as implementers of the curriculum.